Analisis Persepsi Mahasiswa Komunikasi dan Penyiaran Islam IAI AL-AZIS terhadap Penggunaan Tiktok Sebagai Media Dakwah - Hanifah Alma Daniah; Elang Bakhrudin; Alfi Satria (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2025)
This study aims to analyze the role and function of the TikTok application as a social media platform according to students of the Islamic Communication and Broadcasting (KPI) program at IAI AL-AZIS and to examine perceptions regarding its use as a medium for da'wah. This research employs a qualitative approach with a descriptive method. The study subjects consist of KPI students from the 2021, 2022, and 2023 cohorts. Data collection was conducted through interviews and documentation. The findings indicate that TikTok is perceived as a social media platform that plays a role in disseminating information, providing entertainment, fostering creativity, facilitating marketing, and shaping social and cultural trends. Perceptions of da'wah on TikTok are generally positive, with cognitive, affective, and conative components reflecting an understanding of its potential, interest in its content, and engagement in sharing religious messages. TikTok is considered an effective da'wah medium when content is presented creatively, communicatively, and in an easily comprehensible manner, with an emphasis on positive values that align with the communication patterns of the younger generation. Thus, TikTok holds strategic potential in supporting Islamic da'wah in the digital era.